Från det livskraftiga lantbruket till det olönsamma : en studie av skäl till minskad verksamhetsomfattning och varför man bor kvar - Lindström, Rebecka (SLU/Dept. of Urban and Rural Development, 2011)

(untitled)
This essay is a study that contributes to the larger research question “Why do farms shut down?” The subject was chosen because it is a relevant problem that needs to be studied more. This study's boundary is to investigate the reasons for decisions leading to the farms at the Torstuna community, Fjärdhundra, changes in any activity scale or the outlook of the entire farm. When a decision is made, there are usually several reasons behind it and it is these reasons which this essay is aiming to study. The question "What are the reasons for the elderly to live on the farm even though the farm is not cultivated by them?" is also covered in the study. The essay is based on interviews and a study of literature, the results of the interviews included the fact that all farms which were interviewed had ceased livestock production, half of them were leasing out their arable land, all had bad faith in the future on the farms but the majority had nevertheless hope that the farm would remain in the family and that it in the future will be profitable to be a farmer. My conclusions of this study include that decision for ceased or reduced activity level on a farm in Torstuna is a mixture of several different reasons, it depends on age, that it is too much work, it is difficult to obtain it viable, that you have to build a new barn in order to continue, no one wants to take over because the scale is too small and there is too much bureaucracy, rules, red tape and paperwork. Reasons for the elderly to stay on the farm although they are not cultivating the land include that they have a strong sense of the place. The village and the farm is part of their life world which you do not want to leave and there is still hope left that the farm will remain in the family.